CO2 reforming of methane to syngas over highly active and stable supported CoOx (accompanied with MgO, ZrO2 or CeO2) catalysts - Mondal, Kartick C.; Choudhary, Vasant R.; Joshi, Upendra A. (Applied Catalysis A-General, 2007)
{Catalytically inactive CoOx-MgO (calcined at 900 degrees C) becomes highly active and selective in the CO2 reforming of methane to syngas when it is deposited on a commercial low surface-area macro-porous silica-alumina support (SA-5205) or when CoOx is deposited on the support precoated with MgO. Both the supported CoOx and MgO containing catalysts (CoOx -MgO/SA-5205 and CoOx/MgO/SA-5205) show high methane conversion (> 98%) activity and H-2 selectivity (> 94%) and also high stability against carbon deposition [
Keywords: arylboronic acids; diarylmethylidenefluorene; dibromomethylidenefluorene; Pd-mediated coupling; Suzuki reaction

Bentonite - Clay - supported cuprous iodide nanoparticles (BENT- CuI NPs): a new heterogeneous catalyst in diversity - oriented synthesis of 1, 2, 3-triazoles in aqueous medium - Chavan, V, Pramod; Charate, Shrinivas P.; Desai, V, Uday; Rode, V, Chandrashekhar; Wadgaonkar, Prakash P. (Chemistryselect, 2019)
Bentonite clay supported cuprous iodide nanoparticles (BENT-CuI NPs) were prepared and demonstrated for the first time as an efficient heterogeneous catalyst in diversity oriented, green synthesis of 1,2,3-triazoles by one-pot, three component reaction between alkyl halides, arylboronic acids, or epoxides with alkynes and sodium azide in aqueous medium. The catalyst was characterized by Inductively Coupled Plasma Atomic Emission Spectroscopy (ICP-AES), Energy Dispersive X-ray Spectroscopy(EDS), Scanning Electron Microscopy (SEM), X-Ray Powder Diffraction (XRD), Transmission Electron Microscopy (TEM) as well as Brunauer-Emmett-Teller (BET) techniques and was found to be reusable for five consecutive runs without significant loss of activity.
Keywords: 1; 2; 3-triazoles; arylboronic acids; click synthesis; epoxides; green chemistry; heterogeneous catalyst